Establishment and Optimization of Radiomics Algorithms for Prediction of KRAS Gene Mutation by Integration of NSCLC Gene Mutation Mutual Exclusion Information - Wang, Jingyi; Lv, Xing; Huang, Weicheng; Quan, Zhiyong; Li, Guiyu; Wu, Shuo; Wang, Yirong; Xie, Zhaojuan; Yan, Yuhao; Li, Xiang; Ma, Wenhui; Yang, Weidong; et al. (Frontiers in Pharmacology, 2022)
Purpose To assess the significance of mutation mutual exclusion information in the optimization of radiomics algorithms for predicting gene mutation. Methods We retrospectively analyzed 258 non-small cell lung cancer (NSCLC) patients. Patients were randomly divided into training (n=180) and validation (n=78) cohorts. Based on radiomics features, radiomics score (RS) models were developed for predicting KRAS proto-oncogene mutations. Furthermore, a composite model combining mixedRS and epidermal growth factor receptor (EGFR) mutation status was developed. Results Compared with CT model, the PET/CT RS model exhibited higher AUC for predicting KRAS mutations (64.30.834 vs 0.770). By integrating EGFR mutation information into the PET/CT RS model, the AUC, sensitivity, specificity, and accuracy for predicting KRAS mutations were all elevated in the validation cohort (0.921, 0.949, 0.872, 0.910 vs 0.834, 0.923, 0.641, 0.782). By adding EGFR exclusive mutation information, the composite model corrected 64.3% false positive cases produced by the PET/CT RS model in the validation cohort. Conclusion Integrating EGFR mutation status has potential utility for the optimization of radiomics models for prediction of KRAS gene mutations. This method may be used when repeated biopsies would carry unacceptable risks for the patient.